Comunicação pública e campanhas nacionais de vacinação em contexto de midiatização: as estratégias comunicacionais do Ministério da Saúde na crise da cobertura vacinal de 2018 - Motta, Johnny Ribas da (2020)
This dissertation is inserted in a crisis scenario that affects Brazilian public health, especially as recent discussions about vaccination coverage rates and a difficulty in raising awareness of public campaigns applied in the institutional dimension of the Ministry of Health. This proposal is presented in the contemporary challenges brought by social changes, as well as the possibilities of interaction and participation made possible by New Technologies of Information and Communication. Give this, this research aims to analyze the communication strategies in digital media used by the Ministry of Health for a National Vaccination Campaign against Polio and Measles in 2018, as well as understand how the processes are activated in tune with the public communication. It is considered that when dealing with public communication and vaccination campaigns, there is a need to reflect on the exercise of citizenship, which are related to the right to health, information and communication, regarding institutional social rights. Based on the above, the conceptual framework was constituted from Bibliographic Research (LAKATOS; MARCONI, 2003), in order to theoretically subsidize the problematization of the object under analysis, as well as elucidate the proposed objectives. In this sense, the theoretical path was elaborated from three chapters: Chapter 2 - Public Interest, Citizenship and Health; Chapter 3 - Between the Sphere of Public Visibility and Media Visibility and Chapter 4 - The Dimensions of Public Communication, in addition to the subdivisions that complement and support the arguments presented. This research is based on the theoretical-methodological contributions of the basic (SILVA, 2004) qualitative research (MINAYO, 2001) and the exploratory-descriptive approach (GIL, 2007), using as a research method the single case study with integrated units of analysis and triangulation of multiple sources of evidence (YIN, 2010). This research is based on the theoretical-methodological contributions of the basic (SILVA, 2004) qualitative research (MINAYO, 2001) and the exploratory-descriptive approach (GIL, 2007), using as a research method the single case study with integrated units of analysis and triangulation of multiple sources of evidence (YIN, 2010). Data collection was performed based on Documentary Research (CELLARD, 2008), Bibliographic Research (LAKATOS; MARCONI, 2003), Research on Interaction Mechanisms (FERBER; FOLTZ; PUGLIESE, 2017) and In-depth Interview (DUARTE, 2010). As an analysis technique, the strategy of triangulation of methods and techniques was also used, composed of the Codification Cycles (SALDAÑA, 2013), Historical-descriptive Analysis (DEVITO, 1997) and Descriptive Analysis (TRIVIÑOS, 2011). In addition, this study made it possible to understand that the strategies undertaken by the Ministry of Health during the 2018 campaign favored information over communication. As it turned out, the information - in quantity - was widely disseminated, but they disregarded the process as something broader than the. In addition, it was found that the strategies did not privilege the citizen as the center of the communication processes. The lack of dialogue in the construction of campaigns and the lack of interaction in the content published in digital media demarcate the communicational praxis analyzed, which makes it possible to conclude that the strategies employed did not assume the complexity of the practice of public communication. It is emphasized that the establishment of a dialogic communication praxis of stimulating role, to exchanging roles in a rational and co-responsible way can act in strengthening the bond between state and citizen, as well as work in the promotion of full citizenship and mobilizing active society.